The Relationship Between Sleep Quality and Body Mass Index with Work Fatigue in Male Production Workers at PT. Moya Kasri Wira East Java - Fajar Alifka Hadi; Boy Isma Putra (Universitas Muhammadiyah Sidoarjo, 2022)
From the results of initial observations at PT Moya Kasri Wira Jatim in the process of setting the quality target of ice blocks, so that the workforce working in the company must meet the targets. Of the 26 male workers we interviewed experienced fatigue. This is due to the demands of targets that must be met and workers work in a less conducive physical environment, namely a lot of dust that can harm breathing, and working at temperatures high enough so that workers sweat a lot. This study used observational analytics that aimed to see the relationship between Fatigue with Body Mass Index (BMI) and Sleep Quality. The result indicates that there is significant corelation between BMI and fatigue with significance value p=0,030 < Î± (0,05), and also there is significant relationship between sleeping quality and work fatigue with significance value p = 0,008 < Î± (0,05). So, it is concluded that there is corelation between sleeping quality and BMI with work fatigue.